Increasing productivity and improving livelihoods in aquatic agricultural systems: a review of interventions - Joffre, Olivier M.; Castine, S.A.; Phillips, M.J.; Senaratna Sellamuttu, Sonali; Chandrabalan, D.; Cohen, P. (Springer, 2017)
The doubling of global food demand by 2050 is driving resurgence in interventions for agricultural intensification. Globally, 700 million people are dependent on floodplain or coastal systems. Increased productivity in these aquatic agricultural systems is important for meeting current and future food demand. Agricultural intensification in aquatic agricultural systems has contributed to increased agricultural production, yet these increases have not necessarily resulted in broader development outcomes for those most in need. Here we review studies of interventions that have sought to improve productivity in aquatic agricultural systems in Bangladesh, Cambodia and Zambia. We review evidence of development outcomes from these interventions and the particular role of participatory approaches in intervention design and deployment. There was evidence of increases in productivity in 20 of the 31 studies reviewed. Yet, productivity was only measured beyond the life of the intervention in one case, income and food security improvements were rarely quantified, and the social distribution of benefits rarely described. Participatory approaches were employed in 15 studies, and there was some evidence that development outcomes were more substantial than in cases that were less participatory. To explore the impact of participatory approaches further, we examined five empirical cases. Review and empirical cases provide preliminary evidence suggesting participatory approaches contribute to ensuring agriculture and aquaculture interventions into aquatic agricultural systems may better fit local contexts, are sustained longer, and are more able to deliver development benefits to those most in need. A worthy focus of future research would be comparison between outcomes achieved from interventions with differing levels of participation, and the social differentiation of outcomes.